DIGITAL TECHNOLOGY AND PERFORMANCE APPRAISAL - Sukeevong , Watcharapong; Chirinang, Pensri (Journal of MCU Nakhondhat, 2023)
This academic article aims to explain the role of digital technology in the application of performance evaluation. It discusses the meaning and importance of performance evaluation and the process involved. Digital technology in human resource management is used to improve the clarity and effectiveness of performance evaluation, reduce conflicts, eliminate vague evaluation criteria, and decrease redundant data. This article also proposes the use of digital technology in performance evaluation by selecting appropriate tools from the Digital 4.0 era, which are suitable for the organization and applying them to the three evaluation processes: 1) setting performance standards and measures, 2) determining evaluation methods and procedures, and 3) planning development and improvement of performance behavior. Employees in the organization should possess the necessary digital skills, namely using, understanding, creating, and accessing digital technology efficiently. Applying digital technology in performance evaluation results in a fair evaluation system, which is widely accepted by employees, and it clarifies the evaluation criteria. The results of performance evaluation can be used to improve the organization's performance.